[18F]FET-PET Imaging for Treatment and Response Monitoring of Radiation Therapy in Malignant Glioma Patients – A Review - Götz, Irina; Grosu, Anca L. (Frontiers in Oncology, 2013)
In the treatment of patients suffering from malignant glioma, it is a paramount importance to deliver a high radiation dose to the tumor on the one hand and to spare organs at risk at one the other in order to achieve a sufficient tumor control and to avoid severe side effects. New radiation therapy techniques have emerged like intensity modulated radiotherapy (IMRT) and image guided radiotherapy (IGRT) that help facilitate this aim. In addition, there are advanced imaging techniques like PET and PET/CT which can help localize the tumor with higher sensitivity, and thus contribute to therapy planning, tumor control and follow up. During follow up care, it is crucial to differentiate between recurrence and treatment-associated, unspecific lesions, like radiation necrosis. Here, too, PET/CT can facilitate in differentiating tumor relapse from unspecific changes. This review article will discuss therapy response criteria according to the current imaging methods like MRI, CT and PET/CT. It will focus on the significance of PET in the clinical management for treatment and follow up.